1997
DOI: 10.1021/jf960761e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lead Contamination in Spanish Wines and Other Alcoholic Beverages by Flow Injection Atomic Absorption Spectrometry

Abstract: A rapid, accurate, and precise method is described for the direct determination of lead in wine and other alcoholic beverages, using a flow injection−hydride generation−atomic absorption spectrometry system (FI-HG-AAS). Lead hydride was generated in HNO3−H2O2 medium using NaBH4 as the reducing agent. To increase the efficiency of lead hydride generation and to produce mineralized samples, a microwave oven was coupled on-line to the FI-HG-AAS system for some samples. This method was used with 70 samples of wine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 16 publications
2
46
0
1
Order By: Relevance
“…Sensitive techniques, such as flame atomic absorption spectrometry (FAAS), graphite furnace atomic absorption spectrometry (GFAAS), atomic fluorescence spectrometry (AFS), inductively coupled plasma-optical emission spectrometry (ICP-OES), inductively coupled plasma-mass spectrometry (ICP-MS), and potentiometric and voltammetric methods, are required for accurate determination of metals in various samples (Mena et al 1997;Onianwa et al 1999;Karadjova et al 2002;Ibanez et al 2008;Rodriguez et al 2010;Ivanova-Petropulos et al 2013;Ly et al 2013;FroesSilva et al 2015;Seeger et al 2015). Analysis is performed directly on undiluted samples, after a water dilution, or after digestion in open/closed vessel systems with HNO 3 , HCl, H 2 O 2 , or their mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive techniques, such as flame atomic absorption spectrometry (FAAS), graphite furnace atomic absorption spectrometry (GFAAS), atomic fluorescence spectrometry (AFS), inductively coupled plasma-optical emission spectrometry (ICP-OES), inductively coupled plasma-mass spectrometry (ICP-MS), and potentiometric and voltammetric methods, are required for accurate determination of metals in various samples (Mena et al 1997;Onianwa et al 1999;Karadjova et al 2002;Ibanez et al 2008;Rodriguez et al 2010;Ivanova-Petropulos et al 2013;Ly et al 2013;FroesSilva et al 2015;Seeger et al 2015). Analysis is performed directly on undiluted samples, after a water dilution, or after digestion in open/closed vessel systems with HNO 3 , HCl, H 2 O 2 , or their mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of lead hydride depends largely on the experimental conditions used, therefore, previous studies have mainly focused on the nature of the acids and oxidizing agents, and their roles in the generation of plumbane. Most common oxidizing agents used in presence of various acids include hydrogen peroxide [6][7][8][9], ammonium or sodium peroxodisulphate [6,10,11], potassium dichromate [6,8,11] and potassium ferricyanide [11,12]. Depending on the type of oxidizing agent, it was reported that the use of acidic oxidizing media increased the reaction rate and sensitivity via efficient oxidation of Pb(II) to an unstable intermediate, Pb(IV), to form plumbane, PbH 4 , [5,6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies of lead hydride generation in wines those that include the batch mode generation of lead hydride with or without mineralization of the samples [9,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The average concentration of Pb in wines from other localities was only 13 μg/L, which is below the average contents of Pb that are reported for some Croatian (46 μg/L, Bukovčan et al, 2009;14 -559 Lazos and Alexakis, 1989). However, the average concentration of Pb in white wines from the Stolac locality, with the exceptions of some Serbian (Suturović and Marjanović, 1998), Ethiopian (Woldemariam and Chandravanshi, 2011), Spanish (Mena et al, 1997), and Cretan wines (Galani-Nikolakaki et al, 2002), was higher than its concentration in wines reported in the available literature. Copper was found in 20 out of 24 analysed wines, with an average concentration of 482 μg/L.…”
Section: Concentrations Of Metals In Winesmentioning
confidence: 59%
“…In the recently available literature many results on concentrations of these seven metals in wines from different countries could be found. A number of researchers reported concentrations of Pb, Cu, and Zn (Lazos and Alexakis, 1989;Marin and Ostapczuk, 1992;Mena et al, 1997;Suturović and Marjanović, 1998;Galani-Nikolakaki et al, 2002;Kristl et al, 2003;Orescanin et al, 2003;Lara et al, 2005;Catarino et al, 2008;Galgano et al, 2008;La Pera et al, 2008;Bukovčan et al, 2009;Voica et al, 2009;Volpe et al, 2009;Kostić et al, 2010, Ražić andOnjia, 2010;García-Rodríguez et al, 2011;Tariba et al, 2011a;Tariba et al, 2011b;Woldemariam and Chandravanshi, 2011;Calin et al, 2012;Sen and Tokatli, 2014). Concentrations of Mn, Cr, and Ni are somewhat less frequently reported (Eschnauer, 1982;Lazos and Alexakis, 1989;CabreraVique et al, 1997;Lendinez et al, 1998;Teissèdre et al, 1998a;Galani-Nikolakaki et al, 2002;Kristl et al, 2003;Orescanin et al, 2003;Lara et al, 2005;Catarino et al, 2008;Galgano et al, 2008;Bukovčan et al, 2009;Voica et al, 2009;Volpe et al, 2009;Ražić and Onjia, 2010;García-Rodrígue...…”
Section: Introductionmentioning
confidence: 99%